2023
DOI: 10.3390/powders2020028
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Cramped-Impact-Type Mechanical Action on Active Pharmaceutical Ingredient (Levofloxacin)—Prospects for Pharmaceutical Applications

Elena Uspenskaya,
Anastasia Simutina,
Ekaterina Kuzmina
et al.

Abstract: Mechanochemistry is one of the ten great discoveries of green chemistry methods for synthesizing new substances. A drug substance from the fluoroquinolone group was exposed to high-intensity mechanical impacts using a laboratory knife mill for 21 min and constantly monitored by analyzing samples extracted every 3 min with DLS, SLS, LALLS, 2D-LS, optical and digital microscopy, FTIR, and Spirotox methods. A dispersity phenomenon was detected in an area where catastrophic dislocations formed and multiplied via l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The figure shows the dispersity phenomenon (DPh) previously described in [ 40 , 41 , 42 , 43 , 44 ]. In this study, the DPh phenomenon is observed in the increase in diameter (d, μm) and volume fraction (%) of size groups of Lcs particles in the ongoing micronisation process at high-intensity ML applied to the solid.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The figure shows the dispersity phenomenon (DPh) previously described in [ 40 , 41 , 42 , 43 , 44 ]. In this study, the DPh phenomenon is observed in the increase in diameter (d, μm) and volume fraction (%) of size groups of Lcs particles in the ongoing micronisation process at high-intensity ML applied to the solid.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, the micronisation of Lcs particles is accompanied by deformation and aggregation of crystals, amorphization and formation of centres with increased activity, which can result in increased reactivity [46]. The figure shows the dispersity phenomenon (DPh) previously described in [40][41][42][43][44]. In this study, the DPh phenomenon is observed in the increase in diameter (d, µm) and volume fraction (%) of size groups of Lcs particles in the ongoing micronisation process at high-intensity ML applied to the solid.…”
Section: Static Light Scatteringmentioning
confidence: 99%
“…The one of the real (6-decarboxylated) Lvf chemical structure derivatives were obtained by tribochemical method based on the intensive impact and cutting loads on the solid [39]. For this purpose, a Stegler LM-250 milling mechanoactivator with a brush motor (Shenzhen Bestman Instrument CO., Ltd., Shenzhen, China), rotation speed 28,000 rpm, power 13 kW, was used.…”
Section: Equipment For Tribochemical Processingmentioning
confidence: 99%